Association Between the Non-High-Density Lipoprotein Cholesterol-to-High-Density Lipoprotein Cholesterol Ratio (NHHR) and Mortality in Patients with COPD: Evidence From the NHANES 1999–2018 - Zhong Y; Zhou K; Li S; Zhang R; Wang D (International Journal of COPD)
Yuhua Zhong,1 Kesi Zhou,2 Sheng Li,1 Renzi Zhang,1 Daoxin Wang1 1Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Anesthesiology, Sichuan Second Hospital of T.C.M, Chengdu, People’s Republic of ChinaCorrespondence: Renzi Zhang; Daoxin Wang, Email zhangrenzi@stu.cqmu.edu.cn; wangdaoxin@hospital.cqmu.edu.cnPurpose: The non-high-density lipoprotein cholesterol-to-high-density lipoprotein cholesterol ratio (NHHR) is a new composite blood lipid index. We aimed to investigate the relationships of the NHHR with mortality from all-causes, cardiovascular disease (CVD), and chronic lower respiratory disease (CLRD) in US patients with COPD.Methods: We assessed the association between the NHHR and mortality via weighted multivariate Cox proportional hazards regression models with restricted cubic splines (RCSs). Between-group survival rates at specific time points were compared via Kaplan‒Meier (KM) curves and Log rank tests. Receiver operating characteristic (ROC) curves were constructed to evaluate the efficiency of the NHHR for predicting mortality risk in COPD patients.Results: After adjusting for confounding factors, weighted multivariate Cox proportional hazards regression model showed that higher NHHR was not significantly associated with all-cause mortality (HRs = 1.74), CVD mortality (HRs = 1.19), and CLRD-related mortality (HRs = 0.65), but HRs tended to increase as NHHR increased. RCS revealed U-shaped associations between the NHHR and all-cause mortality. KM survival analysis revealed a significantly lower survival rate for patients in the high-NHHR group (Log rank test P< 0.001). In addition, the NHHR had superior performance in predicting mortality, with AUC values of 0.85 and 0.883 for all-cause mortality, 0.769 and 0.815 for CVD mortality, and 0.765 and 0.815 for CLRD-related mortality at 5 and 10 years, respectively.Conclusion: The higher the NHHR is, the greater the risk of all-cause mortality in COPD patients. The NHHR was significantly superior to other haematological biomarkers in predicting mortality.Keywords: COPD, NHHR, all-cause mortality, CVD mortality, CLRD-related mortality